Do conscientious employees have a high level of work engagement? The roles of presenteeism and perceived organizational support - Hui Sun; Shuai Wang; Wei Zhang; Ling Sun (Frontiers in Psychology)
In recent years, work engagement garnered significant attention from both the business community and academia. Drawing on conservation of resources (COR) theory, this study investigates the mechanisms and boundary conditions through which conscientiousness influences work engagement. Through an empirical survey of 376 employees, the study found that, first, conscientiousness positively predicts employees’ work engagement; second, presenteeism partially mediates the relationship between conscientiousness and work engagement; third, perceived organizational support (POS) negatively moderates the relationship between conscientiousness and presenteeism while positively moderating the relationship between presenteeism and work engagement; fourth, POS moderates the indirect effect of conscientiousness on work engagement via presenteeism, whereas the mediated relationship is weakened when employees exhibit a higher POS. These findings advance our theoretical and practical knowledge of how personality traits and situational factors jointly affect employees’ work engagement, providing empirical data for a dialectical perspective on conscientious employees and enhancing their work engagement.